WORK AUTONOMY PROFILE OF COUNSELOR: A EDUCATIONAL BACKGROUND BASED APPROACH - Yuca, Verlanda; Magistarina, Elrisfa (Universitas Pendidikan Indonesia, 2024)
Autonomy at work is an important element of employee motivation and involvement in work. Autonomy provides happiness and satisfaction at work for employees so that it can lead to higher productivity. The purpose of this study in general is to describe the profile of work autonomy in the organization directing the picture of employee work autonomy in terms of educational background. In particular, it discusses the forms and patterns of autonomy that have been created and the patterns of autonomy formed based on educational background. The population in this study were counselor at Junior High Schools in West Sumatra Province using the Simple Random Sampling Technique. Data collection uses instruments adopted and modified from Perceived Autonomy Support: The Learning Climate Questionnaire (LCQ). The data analysis approach used is quantitative with descriptive data types. The benefit of this research is that there is an overview of the profile of autonomy in work in terms of educational background. The results found that the counselor's work autonomy was on average in the high category. Suggestions from the results of this study are for counselor to improve and develop the ability to work autonomy so that they can be more comfortable and satisfied with work.